Near-trapping effects for multi-column structures in deterministic and random waves - Grice, JR; Taylor, P; Taylor, R (2013)
Linear theory has been applied to the diffraction of regular waves by square arrays of columns. Free surface amplification has been calculated using the linear module of the computer program DIFFRACT and compared between solitary columns and arrays of two and four columns. Implications of the near-trapping phenomenon for the occurrence of violent responses have been looked at. The effect on free surface amplification of changing column shape and breaking up array symmetry has been studied. The diffraction of NewWave wavegroups by square arrays of circular columns and statistics of extreme events in random sea-states are used to produce a net amplification factor for highlighting probable locations of violent response when designing new structures. © 2012 Elsevier Ltd. All rights reserved.